SIFAT FISIK DAN MEKANIK KOMPOSIT KAYU SEMEN-SERBUK GERGAJI - . Bakri; Endra Gunawan; Djamal Sanusi (PERENNIAL, 2006)
This research aims to find out the effect of cement-saw dust ratio levels on the physical and mechanical properties of produced composites. The physical properties (density, water content, water absorption after the immersion of one hour and 24 hours, and thickness swelling after the immersion of one hour and 24 hours) and mechanical properties (MOE and MOR) were observed according to ISO standards. The results showed that the use of the cement to sawdust ratio of 3 : 1 in producing wood composite with the target density of 1200 kg/m3 resulted in the lowest water absorption and the highest MOE and MOR. The swelling value and MOR of the produced boards were not acceptable, but their water content, water absorption, and MOE parameters were acceptable according to ISO 8335 1997. Key Words : Physical and mechanical properties, cement wood composite, sawdust